Anti-Biofilm Effect of Ampicillin-Loaded Poly (Lactic-co-glycolic Acid) Nanoparticles Conjugated with Lysostaphin on Methicillin-Resistant Staphylococcus aureus - Elahe Norouzi; Seyed Mostafa Hosseini; Babak Asghari; Reza Mahjoub; Ehsan Nazarzadeh Zare; Mohammad-Ali Shahbazi; Fereshte Kalhori; Mohammad Reza Arabestani (Canadian Journal of Infectious Diseases and Medical Microbiology)
Staphylococcus aureus exhibits the capacity to develop biofilms on various surfaces, encompassing both living and nonliving substrates, enabling it to develop resistance against the immune system and antibiotics. Therefore, this bacterium can cause numerous challenges in healthcare and treatment systems. The present study aimed to investigate the ampicillin-loaded PLGA nanoparticles’ effect on preventing the methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation when it is conjugated with lysostaphin. With the use of the double emulsion evaporation technique, nanodrug carriers were created. Physicochemical attributes of the nanoparticles, such as particle size, drug loading, PDI, encapsulation efficiency, zeta potential, efficiency of lysostaphin conjugation, and morphology, were measured. Minimum inhibitory concentration (MIC), well diffusion, and other techniques were used to investigate the effect of the produced nanodrug carrier on strains of S. aureus. A toxicity test was conducted to examine the toxic effects of artificially generated nanomedicines on the L929 fibroblast culture. The nanoparticle average size, zeta potential, PDI, lysostaphin conjugation efficiency and drug loading encapsulation efficiency, and in the optimum PLGA-AMP-LYS (F4) formulation were 301.9 ± 32 nm, 0.261 ± 0.010, −19.2 ± 3.4 mV, 18.916 ± 1.6, and 94.53 ± 3.8, 40%, respectively. After 72 hours, neither the well diffusion nor MIC techniques revealed any discernible variation between ampicillin and nanodrug carriers. The biofilm investigation’s findings, however, indicated that compared to the free drug, the hindering effect of the nanodrug carrier was greater after 72 hours. The toxicity test findings revealed that the synthesized nanodrug had no toxic effects on the cells. Given the excellent efficacy of the nanomedicine carrier established in the present study, applying this technology to combat hospital-acquired infections caused by Staphylococcus bacteria could yield significant benefits in managing staphylococcal infections.